The longest journey in the world. - Morris, William Barrett; Fraser, Betty (New York, Holt, Rinehart and Winston, 1970)
To a little caterpillar a trip across the garden was the longest, most adventurous journey in the world.
Keywords: Caterpillars -- Fiction